2021
DOI: 10.1007/s00210-020-02037-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of renal insufficiency on anticoagulant effects and safety of warfarin in Chinese patients: analysis from a randomized controlled trial

Abstract: This study aimed to analyze the influence of renal insufficiency on the anticoagulant effects and safety of warfarin in Chinese patients. Data on the creatinine levels of participants enrolled in a randomized controlled study were screened and divided into the non-renal insufficiency group, mild renal insufficiency group, and moderate renal insufficiency group, according to the creatinine clearance rate. The primary outcome measures were stable dose and average daily dose of warfarin. Secondary outcome measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Previous studies have demonstrated the influence of renal impairment on the warfarin maintenance dose [16][17][18]. Moreover, the influence of reduced kidney function was associated with lower warfarin doses after accounting for clinical and genetic factors [29].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies have demonstrated the influence of renal impairment on the warfarin maintenance dose [16][17][18]. Moreover, the influence of reduced kidney function was associated with lower warfarin doses after accounting for clinical and genetic factors [29].…”
Section: Discussionmentioning
confidence: 97%
“…Previously, warfarin management was similar for patients with renal dysfunction and the general population [15]. However, past studies have demonstrated the influence of renal impairment on warfarin dosing [16][17][18]. Moderate and severe kidney impairments have been associated with a reduction in warfarin dose requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, our study found that severe RI may be marginally related to the rapidly achieving rst INR target of warfarin (P = 0.057). A multicenter prospective study found that the achieving rst therapeutic time among patients with severe RI was earlier than those without severe RI [24]. Another previous study, involving 1104 patients with nonvalvular atrial brillation (NVAF), showed that increased creatinine clearance was an independent factor for the prolonged achieving rst therapeutic INR time [20].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, it also mediates the occurrence of DDIs, which, in turn, affects the efficacy of drugs. In severe cases, it can lead to adverse reactions and even endanger the lives of patients [ 46 , 47 ]. Therefore, it is necessary to study the effect of kidney disease on renal drug transporters.…”
Section: Effect Of Kidney Disease On Renal Drug Transportersmentioning
confidence: 99%